Erratum to Jeon et al. "Genetic association of five plasminogen activator inhibtitor-1 (PAI-1) polymorphsms and idiopathic recurrent pregnancy loss in Korean women" (Thromb Haemost 2013; 110: 742-750) (Thrombosis and Haemostasis, 2013)
In the original article by Jeon et al. "Genetic association of five plasminogen activator inhibtitor-1 (PAI-1) polymorphsms and idiopathic recurrent pregnancy loss in Korean women" (Thromb Haemost 2013; 110: 742-750) data in two columns shifted in Table 2. The corrected table is printed here and has also been corrected in the online file.